Harmonization and streamlining of research oversight for pragmatic clinical trials. (October 2015) - O'Rourke, P Pearl; Carrithers, Judith; Patrick-Lake, Bray; Rice, Todd W; Corsmo, Jeremy; Hart, Raffaella; Drezner, Marc K; Lantos, John D
The oversight of research involving human participants is a complex process that requires institutional review board review as well as multiple non-institutional review board institutional reviews. This multifaceted process is particularly challenging for multisite research when each site independently completes all required local reviews. The lack of inter-institutional standardization can result in different review outcomes for the same protocol, which can delay study operations from start-up to study completion. Hence, there have been strong calls to harmonize and thus streamline the research oversight process. Although the institutional review board is only one of the required reviews, it is often identified as the target for harmonization and streamlining. Data regarding variability in decision-making and interpretation of the regulations across institutional review boards have led to a perception that variability among institutional review boards is a primary contributor to the problems with review of multisite research. In response, many researchers and policymakers have proposed the use of a single institutional review board of record, also called a central institutional review board, as an important remedy. While this proposal has merit, the use of a central institutional review board for multisite research does not address the larger problem of completing non-institutional review board institutional review in addition to institutional review board review—and coordinating the interdependence of these reviews. In this article, we describe the overall research oversight process, distinguish between institutional review board and institutional responsibilities, and identify challenges and opportunities for harmonization and streamlining. We focus on procedural and organizational issues and presume that the protection of human subjects remains the paramount concern. Suggested modifications of institutional review board processes that focus on time, efficiency, and consistency of review must also address what effect such changes have on the quality of review. We acknowledge that assessment of quality is difficult in that quality metrics for institutional review board review remain elusive. At best, we may be able to assess the time it takes to review protocols and the consistency across institutions.